Relation between the chemical composition of the seed and oil quality of twelve accessions of Ricinus communis L. - Vasco Leal, José F.; Hernández- Rios, Ismael; Méndez-Gallegos, S. de J.; Ventura-Ramos, Eusebio Jr.; Cuellar-Núñez, M. L.; Mosquera-Artamonov, José D. (Revista Mexicana de Ciencias Agrícolas, 2017)
Castorbean (Ricinus communis L.) is a plant that has generated great interest worldwide due to the oil content extracted from the seed, it can be used in biofuel production, pharmaceutical and cosmetic products, among others. However, in México few studies describe the chemical characteristics of the seed and its oil. The aim of this paper was to determine the proximal chemical composition and oil quality of twelve accessions of R. communis from the states of Aguascalientes, Jalisco, San Luis Potosí and Zacatecas, collected in 2013. A proximal chemical analysis was performed following the techniques recommended by the AOAC (2002) and the quality of the oil was determined by parameters such as viscosity, density, acidity index (IA) and percentage of free fatty acids (%AGL). The data obtained showed that there is significant difference (p< 0.05), in the chemical composition and oil quality, except for the accessions density. SLPS11C1 showed higher oil content (51.04 ±0.44%) and protein (16.02 ±0.36%), while JAL3C1 had a higher crude fiber average (21.15 ±0.16%). AGSS2C1 showed higher viscosity (265.84 ±2.54 mm² s-1) and SLPS11C1 a lower IA (0.5415 ±0.0168 mgKOH g-1) and (%) AGL (0.0272 ±0.0008%). The results suggest that SLPS11C1 and AGSS2C1 are useful accessions for agroindustrial production. However, it must be taken into account that phenological factors may affect the chemical composition of the seed and the quality of the oil independently to the place of origin.